PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM PEMBERANTASAN SARANG NYAMUK (PSN) DALAM MENURUNKAN ANGKA KEJADIAN DEMAM BERDARAH DENGUE DI KELURAHAN PERUMNAS I PONTIANAK - Tedy Dian Pradana; Ade Mayang Saraswati (Jurnal Buletin Al-Ribaath, 2016)
World health organization (WHO) noted country Indonesia as a country with cases of dengue hemorrhagic fever (DHF) is the highest in Southeast Asia. Since 2011 in Indonesia dengue hemorrhagic fever (DHF) has claimed 595 lives out of a total of 65 432 patients person (CFR: 0.91). Dengue cases in Perumnas 1 spread to almost every pillar residents and the average affects children of school age and pre-school age and a rise in cases is high enough that in 2012 and 2013 respectively 5 and 10 cases increased to 27 cases in 2014. Community development program in the village Perumnas 1 is one effort that can be done to decrease the incidence of dengue. Based on the results of community service that has been done in the village river ox outside districts pontianak west can be concluded as follows: top priority health problems that exist in Sungai Jawi Luar Village outside is DHF, the determinant factors associated with the incidence of dengue is the knowledge, the priority problem-solving DBD in villages outside the ox river is education about dengue, establishment coordinator jumantik, film screenings dengue, DHF distribution of leaflets, posters DBD, results of evaluation of health education activities about dengue managed to increase public knowledge about dengue. Advice to Sungai Jawi Luar Village goverment should cooperate with the clinic in implementing health programs and call or invite the citizens to keep the environment with activities of mutual cooperation. Keywords: Community Empowerment, Mosquito Nest Eradication